Effects of Herbal Compound (IMOD) on Behavior and Expression of Alzheimer's Disease Related Genes in Streptozotocin-Rat Model of Sporadic Alzheimer’s Disease - Bazazzadegan, Niloofar (Adv Pharm Bull, 2017)
Purpose: Sporadic Alzheimer’s disease (AD) accounts for over 95% of cases. Possible mechanisms of AD such as inflammation and oxidative stresses in the brain motivate researchers to follow many therapies which would be effective, especially in the early stages of the disease. IMOD, the herbal extract of R. Canina, T. Vulgare and U. Dioica plant species enriched with selenium, has anti-inflammatory, immunoregulatory and protective effects against oxidative stress. Methods: In this study three AD-related genes, DAXX, NFκβ and VEGF, were chosen as candidate to investigate the neuroprotective effect of the extract by comparing their expression levels in the hippocampus of rat model of sporadic AD, using qPCR in the herbal-treated and control groups. The therapeutic effects on learning and memory levels were evaluated by Morris Water Maze (MWM) test. Results: Gene expression results were indicative of significant up-regulation of Vegf in rat’s hippocampus after treatment with the herbal extract comparing to model group (P-value= 0.001). The MWM results showed significant changes in path length and time for finding the hidden platform in all groups during test and the same change in the treated comparing to the control group in memory level. Conclusion: It could be concluded that the herbal extract may have significant effect on gene expression but not on behavioral level.